Analisis Strategi Pengembangan Biogas Sebagai Energi Alternatif Rumah Tangga Dengan Memanfaatkan Limbah Ternak Kotoran Sapi - Ningrum, Septia; Supriyadi, Supriyadi; Zulkarnain, Zulkarnain (Politeknik Negeri Lampung., 2019)
The development of alternative energy which is sourced from cow manure has good prospect to fulfill domestic needs of society. There is one way that can be done by turning farm waste, especially cow manure, to alternative energy as the substitution of fuel in form of biogas. The aim of the study was to analyze developing strategy of biogas as domestic alternative energy by making use of cow manure in Sari Bhakti village, District of Seputih Banyak in Region of Lampung Tengah. The method used in this study was SWOT analysis. Respondents were selected purposively (purposive sampling) from Sari Bhakti village, district of Seputih Banyak with the total sample were 25 cow farmers and 4 experts who have the competence in developing biogas from cow manure. The research finding showed that based on the result analysis of SWOT metrics, recommendation that should be given is ?progressive strategy?. Alternative strategy that can be applied is by utilizing cow farming group to get support from the governance in order to decrease the pollution of environment and to increase the prosperity of society, moreover, increasing socialization of biogas as domestic alternative energy is essential to increase the role of farming group in innovating technology of alternative energy.